2020
DOI: 10.1186/s12906-020-03058-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of selenium-enriched Chrysomyia megacephala (Fabricius) larvae powder and its impact on intestinal microflora in D-galactose induced aging mice

Abstract: Background: The purpose of this study was to assess the antioxidative activity of selenium-enriched Chrysomyia Megacephala (Fabricius) (C. megacephala) larvae powder (SCML) and its impact on the diversity and structure of intestinal microflora in a mouse model of D-galactose (D-gal)-induced oxidative damage. Methods: Sixty male ICR mice were equally randomized to a normal control (NC) group, a model group, a positive group, a low-dose SCML (L-SCML) group, a mid-dose SCML (M-SCML) group, and a high-dose SCML (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
3
7
0
Order By: Relevance
“…Proteobacteria were higher in the C–Se group than in the other groups, showing an increase in this pro-inflammatory phylum in agreement with other studies that reported a significant increase of its abundance in mice fed Se-enriched C. megacephala larvae . We also observed an increased abundance of Tenericutes phylum in Se-supplemented groups, both C–Se and Abx-Se, compared to the non-supplemented groups.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Proteobacteria were higher in the C–Se group than in the other groups, showing an increase in this pro-inflammatory phylum in agreement with other studies that reported a significant increase of its abundance in mice fed Se-enriched C. megacephala larvae . We also observed an increased abundance of Tenericutes phylum in Se-supplemented groups, both C–Se and Abx-Se, compared to the non-supplemented groups.…”
Section: Resultssupporting
confidence: 92%
“…The Lactobacillus group has been observed in higher abundance in mice groups supplemented with Se, even in the antibiotic microbiota-depleted group. In this regard, it has been shown that the Lactobacillus group was increased in diets with median and high Se doses . In addition, the increase of the Lactobacillus genus has also been reported in mice fed a high-fat diet supplemented with Se compared with the un-supplemented group .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the structure and function of the gut microbiota are critically affected by diet [ 6 ]. Increasing evidence suggested that these changes in the level of oxidative stress affected the microbial environment of the intestine and microbiota structure, which eventually caused inflammation and metabolic syndrome in living organisms [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blood deficiency syndrome may be connected with the weak antioxidant capacity of the body [ 17 – 19 ]. The activities of T-AOC and the level of MDA in the liver are commonly detected to assess the antioxidative property in previous studies [ 13 , 20 , 21 ]. In our study, the decreased activity of T-AOC and the increased level of MDA in liver tissues in the model group were observed ( Table 3 ), which was consistent with the blood deficiency model mice in previous studies [ 10 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%